Discretionary trusts and section 7 (5) of the Income Tax Act - Place, C (Department of Commercial Law, 2023)
Discretionary Trusts have fast become a very popular vehicle in all types of business transactions, due to their extremely flexible nature and the lack of formalities required in their day to day administration. However, largely for the above reasons, there are in my submission a great many questions arising from their existence, the answers to which are not always clear. Discretionary Trusts are furthermore, because of their inherent flexibility excellent vehicles for abuse, particularly in the form of tax avoidance. The purpose of this dissertation is to consider the Application of Section 7(5) of the Income Tax Act to a Discretionary Trust, and to attempt to answer what has been described as "the vexed question" of whether the exercise of a Trustee's discretion in a Discretionary Trust constitutes an "event" within the meaning ,of that Section. In addition I have given consideration as to whether "vesting' is a requirement of the operation of Section 7(5).